A new species of the hermit crab genus Cancellus H. Milne Edwards, 1836 from a mesophotic deep bank in the northwestern Gulf of Mexico (Crustacea: Decapoda: Diogenidae) - Felder, Darryl L.; Lemaitre, Rafael (Zootaxa, 2020)
Recent sampling on mesophotic deep banks in the northwestern Gulf of Mexico has produced a previously undescribed hermit crab assignable to the genus Cancellus H. Milne Edwards, 1836. Members of the genus are most often found to occupy cavities of eroded coral, siliceous sponges, porous calcareous rock fragments, algal concretions, or worm tubes as shelters. The present specimen was found loose as by-catch in a dredged rhodolith sample taken for algal life history studies. In situ, it likely occupied a cavity within one of the collected calcareous rhodoliths or small sponges in the by-catch. While our description is based on a single female specimen, the holotype is fully mature and intact, and it was solidly frozen in seawater until its coloration could be photographically documented and tissues extracted for sequencing. In comparison to the three other known western Atlantic species, the frontal rim of the carapace shield in the new species is continuous between the blunt lateral teeth as in C. ornatus Benedict, 1901 and C. viridis Mayo, 1873, and thus distinct from the subdivided front found in C. spongicola Benedict, 1901. The rim itself is somewhat flattened as in C. ornatus rather than inflated as in C. viridis. However, each of the ocular scales bears a pair of spines at the tip, as in C. viridis. The lower palms of the chelipeds, while distinctly rugose, do not have a separated patch of stridulating ridges comparable to those reported for C. spongicola. The yellow-orange to deep-orange pigmentation of the color pattern differs from fresh coloration in both C. ornatus and C. viridis, but that of C. spongicola is unknown for other than preserved specimens. Description of the single available specimen is in this case justified by the low likelihood for timely acquiring of additional samples from the type locality or adjacent habitats, most of which are deep banks warranting protection under pending habitat management changes. Our diagnosis includes GenBank accession numbers for COI sequences to facilitate future molecular phylogenetic comparisons.